Time Budget Pressure Sebagai Pemoderasi Pengaruh Due Professional Care dan Pengalaman Audit Pada Kualitas Audit - Savitri, Dian Indah; Dwirandra, A.A. Ngurah Bagus (E-Jurnal Akuntansi, 2018)
Audit quality is important because high quality will produce reliable financial reports as the basis for decision making. Therefore, the quality of audit is an important thing that must be considered by the auditors in the auditing process. So this study aims to examine the effect of due professional care and audit experience on audit quality with time budget pressure as a moderation variable. This study was conducted at Public Accounting Firm in Bali in 2016. The number of samples taken 62 auditors who are willing to participate in this research. The sample in this research is determined by purposive sampling method. Data were collected using survey method. Data analysis technique used is analysis of Multiple Linear Regression and Moderated Regression Analysis (MRA). This research successfully demonstrated due professional care and audit experience had a positive effect on audit quality. This study also shows the time budget pressure to strengthen the due professional care relationship on audit quality with moderation test results showing a positive effect. The result of moderation testing between audit experience and time budget pressure shows a negative influence which means time budget pressure weakens the relationship between audit experience on audit quality. Keywords: time budget pressure, due professional care, audit experience, audit quality